UPAYA PENCEGAHAN HIV/AIDS PADA WANITA PEKERJA SEKSUAL (WPS) DI KLINIK INFEKSI MENULAR SEKSUAL (IMS) - Viridula, Erike Yunicha; purnani, weni tri; febriyanti, dita; fadila, anita nuril (Jurnal Bidan Pintar, 2021)
The problem that has developed in connection with HIV / AIDS infection is the high incidence and mortality. HIV / AIDS is a virus that causes disease by destroying the body's defense system so that sufferers do not have the ability to defend themselves from disease attacks. The aim of the study was to determine the HIV / AIDS prevention efforts of FSW at the IMS Clinic at the Gurah Health Center, Kediri Regency in 2019.Quantitative descriptive research design. The total population of all FSW who have not been exposed to HIV / AIDS who visited the STI Clinic at the Gurah Health Center, Kediri Regency in 2019. With a sample size of 39 and the sampling technique used accidental sampling. The instrument used was a questionnaire.Efforts to prevent HIV / AIDS among FSW include the use of male condoms where as many as 20 respondents (66.7%) sometimes use condoms, 24 respondents (80%) use condoms either, based on the use of female condoms as many as 21 FSW (70 %) never used, the way to use female condoms was 22 respondents (73.3%) good.It is hoped that health workers will increase the provision of information to the public regarding HIV / AIDS prevention efforts by using condoms so that the HIV / AIDS rate in Kediri Regency can be reduced.